Nontrivial clustering of microseismicity induced by hydraulic fracturing. Issue 20 (21st October 2016) - Maghsoudi, Samira; Eaton, David W.; Davidsen, Jörn
Abstract: For induced microseismicity associated with hydraulic fracturing, the frequency‐magnitude distribution is typically characterized by a falloff with increasing magnitude that is significantly faster than for seismicity along active fault systems. This characteristic may arise from a break in scale invariance, possibly due to mechanical layering that typifies fine‐grained sedimentary rocks in many shale gas and tight oil reservoirs. The latter would imply the presence of spatiotemporal magnitude correlations. Using three microseismic catalogs for well stimulations in widely separated locations with varying hydraulic‐fracturing methods, we show that events with similar magnitudes indeed tend to cluster in space and time. In addition, we show that the interevent time distribution can be described by a universal functional form characterized by two power laws. One exponent can be related to the presence of interevent triggering as in aftershock sequences and is a consequence of the Omori‐Utsu law. The other one is a reflection of the intrinsic spatial variation in the microseismic response rates. Taken together, these features are indicative of nontrivial spatiotemporal clustering of induced microseismicity and, hence, of direct relevance for time‐dependent seismic hazard assessment. Key Points: Magnitudes of microseismic events induced by hydraulic fracturing tend to cluster Interevent triggering is present and follows the Omori‐Utsu law The interevent time distribution exhibits a universal character